A Change in the Amount of CO2 at the Center of the Examination Halls: Case Study of Turkey - Cetin, Mehmet (Kamla Raj Enterprises, 2016)
The performances of candidates during the exam period depend on several factors, such as the temperature in exam halls. The indoor amount of CO2 is over 1000 ppm, which in turn, could directly affe...